Tunable luminescence properties of GeO2-Doped Li2ZnTi3O8: Mn4+ red phosphor. (January 2023) - Tseng, I-Wei; Tsai, Meng-Hung; Hsu, Tsung-Hsien; Lin, Che-An; Lin, Shih-Kang; Huang, Cheng-Liang
Highlights: Simulated data exhibited that energy transition can be easily achieved between Mn and Ge, and the potential application in the excitation of blue light. The exchange interaction dominates the energy transfer mechanism. A profound promotion achieved in the emission intensity on the 0.4% GeO2 -doped phosphors. Abstract: Ab initio calculation of density of states and the absorption spectral analysis were performed, and the influence of doping Mn 4+ activator and Ge 4+ sensitizer on the photoluminescence properties was also successfully discussed. The critical concentrations of Mn 4+ and Ge 4+ in Li2 ZnTi3 O8 host excited at 350 nm were determined to be 0.3 and 0.4 %, respectively. The results obtained in this study indicated that there was a 50 % promotion in the emission intensity in the 0.4 % GeO2 -doped phosphors when compared to the performance of undoped Li2 ZnTi3 O8 : 0.3 % Mn 4+ phosphors. Moreover, the International Commission on Illumination of Li2 ZnTi3 O8 :0.3 % Mn 4+ point was successfully turned from (0.7268, 0.2732) to (0.7318, 0.2682), and the color purity - from 98.3 to 99.5 % by co-doping 0.4 % GeO2 . The energy transfer mechanism (Mn 4+ ---Mn 4+ pairs, and Ge 4+ ---Mn 4+ pairs) was also investigated. Concentration and thermal quench were also under consideration.